E-Diwan ingenious mobile interactive Arabic language education tool - Ahmad H.Osman, Rahmah; Md Ghalib, Mohd. Feham; Mahmud, Murni; Ahmed Mahmoud, Ahmad Ragheb (Centre for Teaching and Learning (CTL) and International Islamic University Malaysia (IIUM), 2018)
Arabic language is a global language and has become one of the most important languages for all language learners around the world. A fundamental component of sound Arabic language acquisition is Arabic poetry which is innately intricate. Hence, deficiency in interactive computer programs specially designed for learning Arabic poetry, has generated apathy that Arabic poetry is superfluous, consequently ensuing impotence to the graduates of Arabic Language and Literature Studies. The existing scenario illustrates the preference and reliance on interactive programs and gadgets among the educators and students. E-Diwan enables the accessibility of teaching and learning Arabic poetry through a mobile device and a mobile interface (Android, iPhone, Windows Mobile) with a designated Arabic poetry electronic portfolio website. E-Diwan keeps the students glued to the screen and are dazzled by the atheistic beauty of Arabic poetry subsequently augmenting them with a corpus of Arabic literary lexis. By a click of a button, the app displays a spectrum analysis of the poems; definition, grammatical and rhetorical properties, a brief biography of the poet, and translation of the poems in English and Malay. It is also equipped with the ability to audio present the above information using a recorded voice of an Arabic native speaker. Built-in are videos designed to simultaneously improve the information outcome and performance skills of the user. E-Diwan’s comprehensive nature facilitates individual learning, which cultivates Life Long Learning. E-Diwan fits as a lecture companion tool for all educators teaching Arabic poetry and Arabic language learners.